Mathematical Methods of Operations Research - Stein, Oliver; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
This peer reviewed journal publishes original and high-quality articles on important mathematical and computational aspects of operations research, in particular in the areas of continuous and discrete mathematical optimization, stochastics, and game theory. Theoretically oriented papers are supposed to include explicit motivations of assumptions and results, while application oriented papers need to contain substantial mathematical contributions. Suggestions for algorithms should be accompanied with numerical evidence for their superiority over state-of-the-art methods. Articles must be of interest for a large audience in operations research, written in clear and correct English, and typeset in LaTeX. A special section contains invited tutorial papers on advanced mathematical or computational aspects of operations research, aiming at making such methodologies accessible for a wider audience. All papers are refereed. The emphasis is on originality, quality, and importance. Officially cited as: Math Meth Oper Res Jointly sponsored by Gesellschaft fuer Operations Research - The German OR Society Nederlands Genootschap voor Besliskunde - The Dutch OR Society.
Keywords: Business; Management science; Operations research; Decision making; Calculus of variations; Calculus of Variations and Optimal Control; Optimization; Operations Research/Decision Theory; Business and Management, general